INOVASI LAYANAN PERSIAPAN PERSALINAN (EDUKASI DAN SENAM HAMIL) PADA IBU HAMIL DI WILAYAH KERJA UPT PUSKESMAS ALAS BARAT KABUPATEN SUMBAWA - Setianingsih, Fitri; Atmasari, Ayuning; Taryono (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
The labor process is influenced by three factors, namely Passage (birth canal), Passanger (fetus), Power (strength). Childbirth can run normally if all three factors are met properly. In addition, there are other factors that affect the delivery process, namely psychological and helper. Maternal Mortality Rate (MMR) can be reduced by various efforts, both promotive and preventive, by providing education in preparation for childbirth. This education can be an alternative for pregnant women to find out the extent of maternal and fetal development, increase maternal independence and train coping management for maternal stressors. Pregnancy exercise is a form of coping method that can avoid the occurrence of physical stress due to pregnancy, such as reducing leg and back cramps, increasing the mother's ability to adapt to changes in her body. This study aims to identify the effect of labor preparation services (pregnancy education and exercise) on the preparation for delivery of pregnant women in the working area of ??the UPT Puskesmas Alas Barat. Pre-experimental research design with one group pretest-post test design. The instrument used for data collection is a questionnaire. Testing the instrument using the product moment person validity test and reliability test. The analysis used is simple linear regression with the number of respondents as many as 102 pregnant women. The results showed that the regression significance value of the delivery preparation service variable (pregnancy education and exercise) on the preparation for delivery of pregnant women was 0.000 or less than 0.05. The hypothesis which states that delivery preparation services (pregnancy education and exercise) has an effect on preparation for delivery of pregnant women (accepted). Based on the results of this study, it can be suggested that pregnant women play an active role in participating in activities during pregnancy so that mothers have knowledge about the needs during pregnancy, especially preparation for childbirth so as to minimize emergencies to the mother and fetus during the delivery process.